An analytic model for the epoch of halo creation - Percival, W; Miller, L; Peacock, J (2000)
In this paper we describe the Bayesian link between the cosmological mass function and the distribution of times at which isolated halos of a given mass exist. By assuming that clumps of dark matter undergo monotonic growth on the time-scales of interest, this distribution of times is also the distribution of `creation' times of the halos. This monotonic growth is an inevitable aspect of gravitational instability. The spherical top-hat collapse model is used to estimate the rate at which clumps of dark matter collapse. This gives the prior for the creation time given no information about halo mass. Applying Bayes' theorem then allows any mass function to be converted into a distribution of times at which halos of a given mass are created. This general result covers both Gaussian and non-Gaussian models. We also demonstrate how the mass function and the creation time distribution can be combined to give a joint density function, and discuss the relation between the time distribution of major merger events and the formula calculated. Finally, we determine the creation time of halos within three N-body simulations, and compare the link between the mass function and creation rate with the analytic theory.